Wanted : world financial stability - Fernández-Arias, Eduardo (IDB WashingtonUS, 2000)
Recapitulates what has been learned from previous crises, suggests what individual countries can do to insulate themselves from contagion, and discusses the role international financial institutions can play in providing solutions. Exposes the heated exchange rate debate, the links between exchange rate policy and financial fragility, and the arguments for supranational currencies and dollarization.